Morphology of preimaginal stages of Minettia longipennis Fabricius (Diptera: Lauxaniidae) MAREK SEMELBAUER & MILAN KOZÁNEK (Slovakia) - Semelbauer, Marek; Kozánek, Milan (Zootaxa, 2011)
Scanning electron microscopy documentation of all preimaginal stages of the lauxaniid species Minettia longipennis (Fabricius) is presented for the first time. Images of the following morphological structures of all larval instars are provided: pseudocephalon, antenna, maxillary palpus, facial mask, cirri, mouth hooks, ambulatory lobes, anterior and posterior spiracles. Illustrations of the cephalopharyngeal skeleton for all three instars in lateral, ventral and dorsal views are provided. All instars are clearly separable by morphological features. The first instar has unique modification of the facial mask and structure of the cephalopharyngeal skeleton. Second and third instars are similar in overall form and differ in details in structure of the mouthooks and anterior spiracles, and by the number of pharyngeal ridges.